FlowMon: A Workflow-Driven Visual Tool for Automated Monitoring Script Generation - Lima, Eduardo; Vanderlei, Igor; Araujo, Jean (Anais do Latin-American Symposium on Dependable Computing (LADC); 2025: Anais do XIV Latin-American Symposium on Dependable Computing, 2025)
Computing systems are becoming increasingly complex, which makes it necessary to monitor and manage resources. However, manually creating monitoring scripts is time-consuming, error-prone, and does not scale well with system growth. This paper presents a tool that proposes the automatic generation and execution of Shell Scripts for monitoring computing resources through a workflow-based visual interface. Using an intuitive GUI (Graphical User Interface), users can drag and configure components to be evaluated within a visual flow editor. Linux monitoring commands have been transformed into high-level visual representations of computing resources, allowing users to create and execute their own scripts to monitor local or remote systems with minimal interaction or coding knowledge. To demonstrate that the application works effectively, we conducted practical tests, provided different use cases, and compared it with other tools on the market. The results demonstrated the tool’s effectiveness, showcasing its ability to create and execute Shell Scripts while continuously simplifying the monitoring process and maintaining a low impact on the system.